Translation of scientific text - Hosshanthika, M. (University of Jaffna, 2022)
Purpose: This paper analyses the Translation of scientific text. Scientific translation is also an academic discipline which focuses on the technical aspects. Scientific language is used in expert – expert and expert – lay communication, with characteristics features vary from genre to genre, depending on the communicative situation and its participants. This paper discusses the practical problems concerning the translation of scientific text in a broad outline of formal and natural languages. Methodology: This study is mainly based on the researcher's various readings and knowledge of two languages and few fieldworks. This study consists of descriptive and comparative research methods. These methods helped to analyze the problems the researcher faced. The comparative study was used to compare the source text with the target text. The comparative method consists of the translation schema to compare and contrast the source text and translated text based on the theoretical and ethical features. Meanwhile, the descriptive method is used to deeply identify and explains the character of the scientific translation. Moreover, it examines the translation practice based on the theoretical feature. Findings: Scientific translation encounters many translation challenges itself. Meanwhile some words can be translated easily but some words are difficult to translate. There are various problems occur in translating scientific text from English to Tamil at linguistic, contextual and extra linguistic level. This paper expresses the character of scientific texts and the problems encountered while translating scientific texts from English to the Tamil language. This paper analyses the translation techniques and strategies used in scientific text. Research limitation: This paper explores the features of scientific texts and discusses useful strategies for the translation of this type of text. Further, a large number of scientific texts have been collected and translated into the Tamil language as primary data. Implications:This paper presents some techniques and strategies for the translation of scientific texts according to functional translation theory.
Keywords: English language; Scientific text; Tamil language; Translation